Fiction Factory - Novel - Last Chapter Writing Competition 2022 - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2022)
15 May 2022 – Intelligentsia Club UMP had successfully conducted a Fiction Factory Programme - a writing competition. The programme was held for 2 weeks which started from 23 April until 5 May 2022 via an online platform.